SPIDERS (ARACHNIDA: ARANEI) OF SEASIDE AND ISLAND TERRITORIES OF NORTHERN DAGESTAN - A. V. Ponomarev; G. M. Abdurakhmanov; S. V. Alieva; K. V. Dvadnenko (Юг России: экология, развитие)
Annotated list of spiders species from the seaside and island territories of Northern Dagestan, based on the original material. At the present time 132 species from 20 families are recordet in this region. There are illustrated descriptions of new species Gnaphosa deserta Ponomarev et Dvadnenko, sp. n., similar with G. rufula (L. Koch, 1866) and Ozyptila dagestana Ponomarev et Dvadnenko, sp. n., similar with O. simplex (O. Pickard-Cambridge, 1862) and males Berlandina apscheronica Dunin, 1984, Pardosa jaikensis Ponomarev, 2007 and Tibellus utotchkini Ponomarev, 2008.